Агаарын нөлөөг тооцсон математик дүүжингийн өргөтгөл - Пүрэвдорж, Мөнхбаяр (Scientific transaction of the National University of Mongolia. Physics, 2022)
This paper conducts with the air resistance force in a mathematical pendulum. The pendulum is possible to analyze the effects of air resistance, and it has been compared with the simulation results.